Thermopower and thermal conductivity in the Weyl semimetal NbP. (14th July 2017) - Stockert, U; dos Reis, R D; Ajeesh, M O; Watzman, S J; Schmidt, M; Shekhar, C; Heremans, J P; Felser, C; Baenitz, M; Nicklas, M
Abstract: The Weyl semimetal NbP exhibits an extremely large magnetoresistance and an ultra-high mobility. The large magnetoresistance originates from a combination of the nearly perfect compensation between electron- and hole-type charge carriers and the high mobility, which is relevant to the topological band structure. In this work we report on temperature- and field-dependent thermopower and thermal conductivity experiments on NbP. Additionally, we carried out complementary heat capacity, magnetization, and electrical resistivity measurements. We found a giant adiabatic magnetothermopower with a maximum of 800   μ V   K − 1 at 50 K in a field of 9 T. Such large effects have been observed rarely in bulk materials. We further observe pronounced quantum oscillations in both thermal conductivity and thermopower. The obtained frequencies compare well with our heat capacity and magnetization data.